The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/jep.12671
|View full text |Cite
|
Sign up to set email alerts
|

Applying Lean Six Sigma methodology to reduce cesarean section rate

Abstract: LSS is an effective way to reduce the rate of cesarean section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Internal processes Clinical indicators Reduction in the rate of mechanical ventilation use, in the rate of care-related infection, in surgical complications, in the fall rate, in the number of cesareans, and improvement in the rate of hand hygiene (3,12,20,(26)(27)(28)(31)(32)37,40) .…”
Section: Bsc Perspective Improvement Results For Health Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Internal processes Clinical indicators Reduction in the rate of mechanical ventilation use, in the rate of care-related infection, in surgical complications, in the fall rate, in the number of cesareans, and improvement in the rate of hand hygiene (3,12,20,(26)(27)(28)(31)(32)37,40) .…”
Section: Bsc Perspective Improvement Results For Health Institutionsmentioning
confidence: 99%
“…Applying Lean Six Sigma methodology to reduce cesarean section rate (27) 2016 China Use of LSS to reduce the rate of cesarean section in the hospital.…”
Section: Hospitalmentioning
confidence: 99%
“…A smaller number of mothers prefer the C-section because it is a safer and healthier method for delivery. According to Chai et al (25), a large number of pregnant women prefer the C-section due to fear of pain. The use of anesthesia in the delivery room can be effective in reducing fear.…”
Section: Managing Insurance and Financial Affairsmentioning
confidence: 99%
“…With the Cervical Dilatation of More Than 4 cm Chai et al (25) stated that inappropriate interventions and inadequate training in labor led to an increase in the C-section rate. Dias et al (64) also showed that the hospitalization of less than 4 cm cervical dilatation and the use of analgesics are some of the midwifery factors leading to an increase in C-section rates.…”
Section: The Policies For Admission and Hospitalization Of Womenmentioning
confidence: 99%
“…Six Sigma methodology has been found to reduce the length of hospital stay by minimizing the possible variabilities (9). The rate of cesarean section in pregnancy was reported to decrease from 41.83% to 32% by Six Sigma methodology (10). Moreover, Six Sigma methodology has been used in the nursing care of patients with hip fractures (11).…”
Section: Introductionmentioning
confidence: 99%